Spatial variability and pollutant-specific mitigation effects of an urban vegetated park observed with a high-density air quality sensor network - Jongwon Ryu; Taehun Lee; Yongmi Park; Subin Han; Jaehun Park; Jae-Jin Kim; Wonsik Choi (Environmental Pollution, 2026)

Influence of sea–land breeze circulation on PM2.5 variability and chemical composition in five coastal cities of South Korea - Yongmi Park; Subin Han; Seongmin Seo; Joon-Young Ahn; Changhyeok Kim; Min Hye Jeong; Wonsik Choi (Atmospheric Environment, 2026)

Generation of NOD SCID mice with near-complete deletions of Il2rg and Prkdc for human cancer and HSC engraftment - You-Min Kim; Hee Ju Na; Do Hee Kwon; Jae Hoon Lee; Bo Min Park; Subin Lee; Tae Wook Nam; Mi Yeon Park; Sun Ha Park; Sung Joo Kim; Bongkum Choi; Han-Woong Lee (Transgenic Research, 2025)
Immunodeficient mouse models are invaluable tools for preclinical research, particularly for cancer therapies and studies of the human immune system. Notably, strains with combined Prkdc (scid) and Il2rg (null) mutations—such as NOG and NSG mice— are widely used due to their profound immunodeficiency, allowing efficient engraftment of various human cells. However, these models were generated by disrupting the Il2rg gene through replacement with a neomycin resistance (Neo) cassette in embryonic stem cells. Incomplete excision of this cassette can inadvertently alter the expression of neighboring genes, thereby introducing potential confounding variables. In addition, they may still express mutant mRNAs that escape nonsense-mediated decay (NMD) and/or produce truncated proteins with residual activity, potentially compromising the interpretation of experimental outcomes. To address this, we developed the N2G mouse strain (NOD-2-Genes KO) where almost all genomic loci of both Prkdc and Il2rg genes are deleted via CRISPR/Cas9 genome editing. N2G mice exhibited tumor growth comparable to NOG mice following the transplantation with several human cancer cell lines. Moreover, human CD34 + cord blood (CB) cells engrafted into N2G mice showed robust reconstitution of human immune cells, especially T cells in peripheral blood, spleen and bone marrow, compared to NSG mice. These results suggest that N2G mice, lacking residual mutant mRNA and the exogenous Neo resistant gene, offer an advanced model for preclinical studies.

Millennial-scale depth-resolved ancient microbial diversity and pathogenic potential in Styx Glacier, Antarctica - Minkyung Kim; Hanbyul Lee; Subin Lee; Yeongcheol Han; Ok-Sun Kim (Environmental Research, 2025)

The evolution of physical and chemical properties of PM2.5 in the developing stage of pollution events in a coastal megacity, South Korea - Yongmi Park; Myounghwa Byun; Jaehun Park; Subin Han; Jae-Jin Kim; Youn-Suk Son; Taehyoung Lee; Wonsik Choi (Atmospheric Environment, 2025)

Introducing a novel Standardized Precipitation Evaporation Differential Index (SPEDI) for improved flash drought detection and assessment: a case study in South Korea - Subin Kang; Ho-Jun Kim; Joo-Heon Lee; Hyeon-Cheol Yoon; Hyun-Han Kwon (Stochastic Environmental Research and Risk Assessment, 2025)

Contributions of ambient air, indoor activity, and an air purifier to classroom PM2.5 levels in three elementary schools - Subin Han; Jiwon Kang; Yongmi Park; Jinsoo Kim; Youn-Suk Son; Jae-Jin Kim; Wonsik Choi (Building and Environment, 2025)

Identification of differentially expressed miRNAs involved in vascular aging reveals pathways associated with the endocrine hormone regulation - Jeongwon Jeon; Subin Jang; Ki-Soo Park; Han-Gyul Kim; Jongan Lee; Tae-Sung Hwang; Jin-Sin Koh; Jaemin Kim (Biogerontology, 2025)

Identification and quantification of unreported sialylated N-glycan isomers with α2-3 and α2-6 linkages in the egg yolk protein phosvitin - Subin Yang; Chang Myeong Jeong; Chi Soo Park; Chulmin Moon; Leeseul Jang; Ji Yeon Jang; Han Seul Lee; Kyuran Kim; Haeun Byeon; Daeun Eom; Ha Hyung Kim (Food Research International, 2024)

Rational design of polymer-based insulating scaffolds for high-capacity lithium metal batteries - Jinhyeon Jo; Subin Kim; JunHwa Kwon; Ki-Yeop Cho; Hayong Song; Jaewook Shin; Seung Jong Lee; Wonkeun Kim; Kyoung Han Ryu; KwangSup Eom (Chemical Engineering Journal, 2024)

Estimating vehicular emission factors and vehicle-induced turbulence: Application of an air quality sensor array for continuous multipoint monitoring in a tunnel - HanGyeol Song; Kyucheol Hwang; Ho-Seon Park; Yongmi Park; Subin Han; Myounghwa Byun; Jae-Jin Kim; Joon Geon An; Un Hyuk Yim; Wonsik Choi (Atmospheric Pollution Research, 2023)

Spatiotemporal variability of the PM2.5 distribution and weather anomalies during severe pollution events: Observations from 462 air quality monitoring stations across South Korea - Subin Han; Yongmi Park; Namkyu Noh; Joo-Hong Kim; Jae-Jin Kim; Baek-Min Kim; Wonsik Choi (Atmospheric Pollution Research, 2023)